PERLINDUNGAN HUKUM PARA PIHAK DALAM PERJANJIAN WARALABA MAKANAN - Zil Aidi; Hasna Farida (STIH Putri Maharaja, 2019)
This research aimed to find out and analyze the legal protection of the parties in a food franchise agreement. Furthermore, this research also aimed to find out and analyze the efforts that could be taken by the parties in the event of default in the implementation of the Franchise Agreement. The research that made Sukoharjo Branch Bakso Tengkleng Mas Bambang Branch as a respondent was a juridical empirical qualitative research and analyzed the data collected using qualitative descriptive methods. The results of the research showed that the form of legal protection provided was in the form of preventive and repressive legal protection. Preventive legal protection could be seen in the clause contained in the Tengkleng Mas Bambang Meatball Franchise Agreement which contained the obligations of each party, namely in Articles 5 and 6 concerning the obligation to maintain confidentiality, maintain the brand, and comply with established procedures. Preventive legal protection was also stated in Article 1 number 9 and Article 11 of the Franchise Agreement regarding the prohibition to provide food and beverages other than Tengkleng Mas Bambang Meatballs and trade secrets. Repressive legal protection was seen through the provision of resolving disputes through consensus. If the meeting did not succeed in reaching an agreement then both parties could resolve the dispute through litigation. So far, any form of dispute that occured including defaults could still be resolved through deliberation without taking the path of litigation.